Wizard and glass - King, Stephen (aKing, Stephen 1947- Dark tower, 2017)
aRoland the gunslinger and his crew barely escape one world only to slip into another. It is in this other world that Roland relates to his crew a twisted and entertaining tale of his first quest as a gunslinger and the love of his life, Susan Delgado.